2022
DOI: 10.1038/s41598-022-12964-1
|View full text |Cite
|
Sign up to set email alerts
|

Nudging societally relevant behavior by promoting cognitive inferences

Abstract: Effective behavioral interventions are essential to address urgent societal challenges. Over the past decade, nudging interventions (i.e., arranging the environment to promote adaptive behavioral choices) have surged in popularity. Importantly, effective application of the nudging approach requires clear guiding principles with a firm basis in behavioral science. We present a framework for nudging interventions that builds on evidence about the goal-directed inferential processes underlying behavior (i.e., pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The experiment was designed as a two-stage give-or-take donation game, adapted from Dimant. 30 We conducted the same experiment with the three respective samples in April–June 2020, February–March 2021, and May 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was designed as a two-stage give-or-take donation game, adapted from Dimant. 30 We conducted the same experiment with the three respective samples in April–June 2020, February–March 2021, and May 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the nudge power of identical social information may differ in line with the severity of the disasters. For instance, Wang et al 30 found that the nudging effect of blood users’ demand information was enhanced as the COVID-19 pandemic processes to its peak. However, to our knowledge, no study has explored how the nudge power of identical social information on individuals’ donation behaviors varied with the status of the COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Per these ideas, in recent years, it has been argued that all behaviors (except reflexes), including habitual behavior, are mediated by goal-directed and context-dependent inferential processes (Van Dessel et al, 2022). From this perspective, the mental system supports propositional representations and is geared to make (automatic) inferences (i.e., to activate propositional information based on its compatibility with other propositional information).…”
Section: (Neuro-) Cognitive Mechanisms Underlying Cbmmentioning
confidence: 99%
“…For instance, the training only involves a couple of contexts, behavioral choices, and virtual consequences to choose from and is implemented in an environment with a basic avatar. This approach is probably sub-optimal given that, in inferential theorizing, behavior change requires targeting relevant inferences within a person’s individual network of beliefs (Van Dessel et al, 2022). State-of-the-art approaches and technologies might be introduced to further improve the efficacy of ABC training (or other types of CBM), for example, by implementing training in a virtual reality (VR) setting to improve the immersiveness and reduce boredom.…”
Section: Improvements Of Current Cbmmentioning
confidence: 99%
“…To this end, neuroscience tools can provide an additional implicit measurement when verbalized attitudes and intentions are not consistent with the performed behavior. Behavioral interventions have been focused on the final outcome and therefore do not contribute to the understanding of the mechanisms and factors that underlie the formation of behavior (Van Dessel et al, 2022 ). In order to explore the (implicit) steps before an action takes place, neuroscientific tools could provide an additional asset (Leeuwis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%